The Relationship Between Knowledge Level and Students' Readiness to Face Menarche at the UPTD of SMP Negeri 1 Pesawaran - Mustika, Nabila; Dwiningrum, Riza; Pratiwi, Mida; Sania Rosanti, Afi (LPPM Universitas Dhyana Pura, 2025)
Menarche (the first menstruation) is the culmination of a series of primary and secondary changes, marking the transition of adolescent girls into early womanhood and signifying reproductive organ maturity. The study objective is to examine the correlation between students’ level of knowledge and their readiness to face menarche at UPTD SMP Negeri 1 Pesawaran. The research method used is quantitative with a cross-sectional design. The research was conducted at UPTD SMP Negeri 1 Pesawaran, with a population of 188 students and a sample of 128 respondents from the 7th grade. Data were collected using questionnaires assessing knowledge and readiness to face menarche. Data were analysed using the chi-square test. The results showed that 121 students (94.50%) had good knowledge, 6 students (4.70%) had moderate knowledge, and 1 student (0.80%) had poor knowledge. In terms of readiness to face menarche, 113 students (88.30%) were ready, while 15 students (11.70%) were not ready. The conclusion of this studyindicated that, on average, the students had a good level of knowledge. The statistical test showed a significance value of 0.000 (p < 0.05), indicating a significant correlation between knowledge level and readiness to face menarche. Thus, the study concludeed that the level of knowledge is significantly associated with students' readiness to face menarche at UPTD SMP Negeri 1 Pesawaran.